Analisis Pengelolaan Sistem Jaringan Irigasi Semi Teknis Pada Daerah Irigasi Biangkeke Kecamatan Pajukukang, Kabupaten Bantaeng - Anna, Natalia; Badrun, Burhanuddin; Yusuf, Andi Rumpang (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Provide information on the results of scientific studies on how to improve community welfare by analyzing the Water Needs of semi-technical irrigation networks.The focus of this research is located in Biangkeke, Pajukukang District, Bantaeng Regency. The data needed in the form of secondary data includes land use maps in Bantaeng Regency, RainFall Data, Bantaeng Regency Rain and Bantaeng Regency Climatology Data. The results of the planning analysis obtained a large level of water availability in the Biangkeke irrigation area of 524.36 m3 / second, where in the first period of rice planting was 236.82 m3 / second and for the availability of water in the second period it was 172.63 m3 / second, while in the third period it was 70.90 m3 / second and for the harvest period the available discharge was 44 m3 / second